2018
DOI: 10.1063/1.5037786
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of cation ordering and thermoelastic properties of spinel structure MgGa2O4

Abstract: The coefficient of thermal expansion and elastic stiffnesses of spinel structure MgGa2O4 were determined from 103 K to 1673 K using dilatometry and resonant ultrasound spectroscopy. The state of cation order was investigated on specimens quenched from temperatures up to 1473 K via single-crystal X-ray diffraction. Even at room-temperature, the material is stiffer than what was expected from DFT simulations at 0 K, however, the stiffness falls within the predicted range based on the stiffness of the constituent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…For AB 2 O 4 spinel structure, oxygen ions are cubic close‐packed, and cations occupy 1/8 of the tetrahedral sites and 1/4 of the octahedral sites. According to the previous studies, [ 28 ] MgGa 2 O 4 has a partially inverse spinel structure with an inversion index of between 0.81 and 0.87 at room temperature, indicating the disordered distribution of its metal cations. As a result, the optical, electrical, and optoelectronic properties of MgGa 2 O 4 vary significantly with the components of Mg and Ga cations.…”
Section: Introductionmentioning
confidence: 90%
“…For AB 2 O 4 spinel structure, oxygen ions are cubic close‐packed, and cations occupy 1/8 of the tetrahedral sites and 1/4 of the octahedral sites. According to the previous studies, [ 28 ] MgGa 2 O 4 has a partially inverse spinel structure with an inversion index of between 0.81 and 0.87 at room temperature, indicating the disordered distribution of its metal cations. As a result, the optical, electrical, and optoelectronic properties of MgGa 2 O 4 vary significantly with the components of Mg and Ga cations.…”
Section: Introductionmentioning
confidence: 90%
“…Magnesium gallate (MgGa 2 O 4 ) is a stiff, refractory (melting point ~1930 ℃ ), double oxide, with an intermediate band gap value (~4.9 eV) that makes it possible to produce both insulator and conductive variants, as well as being resistant to decomposition until close to its melting point [1]. In its opaque state, it has various applications, including electronics, energy production, and spintronics [1,2], but the most interesting applications are those that exploit the fact that transparency (in the single crystal state) can be coupled with n-type electronic conductivity [1,3]. For instance, photodetectors, gas sensors, transparent electrodes, solid-state phosphors, waveguides, LEDs, or lasing ion hosts (operation at < 100 K) may be derived from this material [3][4][5][6][7].…”
Section: Introduction mentioning
confidence: 99%
“…The first-principles calculation was performed in the framework of density functional theory (DFT) using the Vienna ab initio simulation package (VASP). , The exchange correlation functional was described by the generalized gradient approximation (GGA) of the Perdew–Burke–Ernzerhof (PBE) functional, and the interaction between ions and electrons was evaluated by the projector augmented wave (PAW) method . The lattice parameters of host crystals were relaxed using a 400 eV cutoff energy and a 5 × 5 × 5 k -point mesh, which deviate slightly from experimentally measured results by −0.27% to 0.34%, except for the MgGa 2 O 4 crystal that deviates by 1.41% due to the large degree of Mg–Ga site inversion in the material realized in the experiment (see more details in Table S1 of the Supporting Information). Actually, it has been reported that the volume decreases as the degree of inversion increases .…”
Section: Methodsmentioning
confidence: 99%